Case report: Long term follow-up of a large unilateral epididymal cyst in a stallion used for teaching: Is this condition associated with infertility? - Silva, Gabriela Fernandes; Cunha, Raquel; Carvalho, Fátima; Ribeiro, Mário; Rocha, António; Amorim, Irina; Guimarães, Tiago (Frontiers in Veterinary Science, 2023)
A 30-year-old Lusitano stallion presented with an enlarged right epididymis. The ultrasound scan revealed a cyst-like formation and the histopathological examination was compatible with epididymal cyst located at the body/tail transition, epididymal spermatocele and sperm granuloma and epididymitis. However, these conditions did not seem to affect the animal's reproductive performance, nor did the semen parameters analyzed over the 8 years after the diagnosis show significant changes. Nevertheless, since the ejaculate contains mostly sperm cells from the tail of the epididymis, where fertile spermatozoa are stored until ejaculated, a deep knowledge of the different conditions that can affect this organ is of the utmost importance.